Que conhecimento explícito da área da fonética/fonologia trabalhar nos ensinos básico e secundário? - Veloso, João (Revista da Associação Portuguesa de Linguística, 2019)
In this text, we propose that formal, explicit teaching of very basic notions of phonetics and phonology is gradually introduced in the teaching of L1. The main arguments in favour of this point of view relate to the well-known beneficial effects of phonological awareness on the learning of writing and reading and to some educational experiences that have proven very effective in this field. We share the view that exposing students to the phonetic/phonological dimension of their own language throughout Basic and Secondary Education is doable and advisable so that a number of teachers and subjects benefit from this exposure: Biology, Philosophy, Literature, among others. A sequential, fixed order for the familiarisation of students with such notions is not presented here, as further research and educational experimentation is needed as to attain a reasonable consensos on this specific point.